Evaluation of Teachers’ Active Listening Training at Madrasah Ibtidaiyah Hidayatul Athfal - Ika Tri Yunianika (STAI Ma'had Aly Al-Hikam Malang, 2022)
The aims of this research are to describe: 1) participants’ satisfaction with active listening training in reaction level, and 2) the effectiveness of active listening training in learning level. This evaluation research used the Kirkpatrick model (4 levels). The research objects who were involved in active listening training were teachers from first to sixth grades in Madrasah Ibtidaiyah (MI) Hidayatul Athfal. Data collection was through questionnaires which were distributed before and after training. Descriptive analysis was used to analyze the data. The evaluation results show that participants were satisfied with active listening training.